Pembinaan Narapidana di Lembaga Pemasyarakatan Klas IIA Bukittinggi dalam Perspektif Perencanaan - Utama, Yoko Adhytia (Jurnal Ilmiah Administrasi Publik, 2016)
Planning for prisoners guidance should be able to overcome the problemsoccurred. At the Correctional Institution Class IIA penitentiary in Bukittinggiplanning do not yet overcome the existing problems. This study aims to know how planning in penitentiary Klas IIA Bukittinggi. Qualitative approach is used to explore what and how planning is conducted. The findings show top down planning and a formality planning have been conducted at prisons Class IIA Bukittinggi.